Assessment of Cysts and Cystic-Like Lesions of the Jaws and Their Effect on Adjacent Structures by Using Cone Beam Computed Tomography (CBCT) - Thair Abdul Lateef; Zainab H. Al-Ghurabi; Huda Moutaz Ismael; Muthanna Kamal Ali (College of Dentistry/ University of Baghdad, 2016)
Background: Preoperative radiographical assessment of the maxillofacial lesions is of a great importance in guiding the surgeon during surgical procedure in reducing post-operative complications. This study highlighted the application of CBCT scan in the assessment of maxillofacial cystic and cystic like lesions as a part of advanced radiology Materials and methods: A total of 20 patients (15 males and 5 females) participated in this prospective study. CBCT scan (Kodak 9500 CBCT) with (DICOM) software utilized to perform scanning to all patients in order to assess lesion extension, morphological features and it's relation to the adjacent vital structures. Results: In this study, the total cystic and cystic like lesions involving the maxilla and mandible were (20) lesions. Statistical analysis of the collected data showed no significant differences between the radiographical records and surgical findings regarding diagnostic accuracy of the lesions. Conclusion: The validity of the CBCT in the assessment of maxillofacial cystic and cystic like lesions was similar to the surgical findings regarding lesion extension, expansion, perforation of buccal/or lingual plates, and relation to the adjacent vital structures